NBDC key message: Encourage innovation by integrating and sharing scientific and local knowledge - International Livestock Research Institute; International Water Management Institute (International Livestock Research Institute, 2013)
This digital story was produced to communicate the key messages resulting from the Nile Basin Development Challenge (NBDC). Key message 2 is to integrate and share scientific and local knowledge and encourage innovation through 'learning by doing'. The Nile BDC aimed to improve the livelihoods of farmers in the Ethiopian highlands through land and water management and was funded by the Challenge Program for Water and Food. The eight key messages constitute a 'new integrated watershed rainwater management paradigm' and are based on the outputs and outcomes of trans-disciplinary scientific research for development. For more information see: http://nilebdc.org